2006
DOI: 10.1097/01.aud.0000224981.60575.d8
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Characteristics of Children with Autism

Abstract: Objectives: The objectives of this study were (1) to describe the auditory characteristics of children with autism relative to those of typically developing children and (2) to describe the test-retest reliability of behavioral auditory test measures with this population of children with autism.Design: Audiometric data were obtained from 22 children diagnosed with autism and 22 of their typically developing peers. The audiologic test battery consisted of behavioral measures (i.e., visual reinforcement audiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
96
3
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 59 publications
11
96
3
6
Order By: Relevance
“…Pure tone thresholds were atypical in half of their subjects, yet this difference was not corroborated by click-or tone-evoked auditory brainstem response recordings. Although Tharpe et al (2006) did not find brainstem deficits, other studies of brainstem integrity have identified aberrant function (McClelland et al 1992;Klin 1993;Maziade et al 2000;Rapin and Dunn 2003;Rosenhall et al 2003;Russo et al 2008 in press). In one study investigating brainstem transcription of F 0 contour in speech in children with ASD, deficient pitch tracking was identified in only a subset of those children, while brainstem function was normal in the other children with ASD (Russo et al 2008 in press).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Pure tone thresholds were atypical in half of their subjects, yet this difference was not corroborated by click-or tone-evoked auditory brainstem response recordings. Although Tharpe et al (2006) did not find brainstem deficits, other studies of brainstem integrity have identified aberrant function (McClelland et al 1992;Klin 1993;Maziade et al 2000;Rapin and Dunn 2003;Rosenhall et al 2003;Russo et al 2008 in press). In one study investigating brainstem transcription of F 0 contour in speech in children with ASD, deficient pitch tracking was identified in only a subset of those children, while brainstem function was normal in the other children with ASD (Russo et al 2008 in press).…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, Gravel et al (2006) showed no behavioral differences in the peripheral auditory system in high-functioning children with autism. Tharpe et al (2006) evaluated both peripheral audiometry and brainstem function in children with autism. Pure tone thresholds were atypical in half of their subjects, yet this difference was not corroborated by click-or tone-evoked auditory brainstem response recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Increased loudness perception of pure tone intensity in children and adolescents with autism, demonstrating the existence of hyperacusis in autism, was reported Khalfa et al [16]. Tharpe et al [17] described auditory characteristics in 22 autistic children and 22 of their typically developing peers. The audiologic test battery consisted of behavioral measures (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…Children with autism demonstrated essentially equivalent results on a battery of physiological auditory tests as those obtained from typically developing children. However, on average, behavioral responses of children with autism were elevated and less reliable relative to those of typically developing children [17]. Jones et al [18] tested auditory discrimination ability in 72 adolescents with ASD (39 childhood autism; 33 other ASD) and 57 IQ and age-matched controls, assessing their capacity for successful discrimination of the frequency, intensity and duration differences in pairs of sounds.…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge is the loud acoustic noise created by the interaction of gradient currents with the main magnetic field during the MRI scan. Children with autism often have auditory sensitivities (Rogers and Ozonoff 2005;Tharpe et al 2006). Thus, the thought of enduring scanner noise may increase anxiety and decrease willingness to participate for both parents and children.…”
Section: Hhs Public Accessmentioning
confidence: 99%